Climate change and suicide epidemiology: a systematic review and meta-analysis of gender variations in global suicide rates - Chen, Dan-Dan; Tu, Jin-Heng; Ling, Ke-Nan; Jin, Xiao-Hong; Huang, Hai-Yan (Frontiers in Public Health, 2025)
BackgroundClimate change is reshaping public health, introducing extreme weather conditions and environmental stressors—such as high temperatures, atmospheric pollution, desertification, and storms (rain, thunder, and hail)—that critically impact mental health. Evidence increasingly links these factors to higher rates of suicide-related outcomes, including suicidal ideation, attempts, and self-harm. Such interactions underscore the importance of understanding how climate-driven mental health risks vary by environmental factor and gender, as gender-specific vulnerabilities shape responses to climate stressors.MethodsBy April 16, 2024, we conducted a comprehensive search of PubMed, Web of Science, Cochrane Library, PsycINFO, Scopus, ProQuest, and Embase. Two researchers independently reviewed studies and collected demographic data, systematically tracking and recording rates of suicidal ideation, suicide attempts, suicide deaths, self-harm, and anxiety. Data were rigorously cross-verified for accuracy and consistency.ResultsThe meta-analysis demonstrated significant associations between climate change variables and mental health outcomes. High temperatures and air pollution were linked to increased suicide attempts (OR: 1.40, 95% CI: 1.34–1.45) and suicide deaths (OR: 1.51, 95% CI: 1.44–1.58), particularly among males. Conversely, atmospheric pollution and desertification correlated with a reduced likelihood of suicidal ideation (OR: 0.73, 95% CI: 0.63–0.85). These findings highlight gender-specific mental health impacts, with females exhibiting higher rates of anxiety and self-harm, underscoring the urgent need for targeted interventions addressing climate-induced mental health risks.ConclusionsThis systematic review and meta-analysis reveal significant gender-specific mental health impacts of climate change, with females experiencing higher rates of anxiety, self-harm, and suicidal ideation, while males show greater incidences of suicide attempts and deaths. These findings emphasize the urgent need for targeted interventions and the integration of mental health services into climate policies to address these gender disparities.Systematic review registrationThis study is registered with PROSPERO [PROSPERO (york.ac.uk)] under the identifier [CRD42024534961].